Daya Suka Kalkun terhadap Hijauan, Dedak Padi dan Ransum Komersial dengan Free Choice Feeding: Palatability Rate of Forages, Rice Bran and Commercial Ration with Free Choice Feeding on Turkey (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2022)
The purpose of this study was to evaluate the consumption of feed ingredients (forage, rice bran and commercial rations) in adult local turkeys using free choice feeding. A total of seven  adult male turkeys  were used in this study, fed  with forage (Musa paradisiaca, Ipomea spp, and Indigofera sp leaves), rice brand and commercial ration. Five kinds of feed ingredients were placed in different feeders in each turkey cage. The fresh cut forage was prepared into small pieces of 1-2 cm. Each feed ingredient was analyzed for nutrient content (moisture content, crude protein, crude fat, crude fiber, NFE (Nitrogen Free Extract), ash and gross energy). The data obtained were analyzed descriptively. The results showed that the most palatability forage by adult native turkeys was ipomea spp, indigofera spp and Musa paradisiaca leaves respectively. The commercial ration was the most preferred feed ingredient of all the feed ingredients tested and was followed by rice bran. Adult local turkeys consumed fresh forage was 62 % and total rice bran and commercial feeds was 38%, resp. Consumption of dry matter forage was 17.59% and total rice bran and commercial rations was  82.41%. It can be concluded that turkey feed  can consist of forage, rice bran and commercial ration.Key words:        free choice feeding, Indigofera sp, Ipomea sp, Musa paradisiaca, native turkey, rice bran